The control of the central government over the censor board, to be or not to be - Shringarpure, Salil; Dharm, Jyoti (International Journal of Psychosocial Rehabilitation, 2020)
Right to freedom of speech and expression is a fundamental right as per Article 19(1) (a) of the Indian Constitution. Exhibition of the motion pictures also falls under the ambit of the fundamental rights. Though, the pre censor ship relating to the motion pictures is not challenged, a critical study has made to point out how the government is getting an unfair influence through the current system of film censorship and how in a way the government is controlling the citizens right of freedom of speech and expression.